Carbohydrate intake and multiple sprint sports: with special reference to football (soccer) - Balsom, P. D.; Wood, K.; Olsson, P.; Ekblom, B. (International Journal of Sports Medicine, 1999)
Six male football players competed in a 90 min game (4-a-side) on two occasions following an exercise and diet (either high- approximately 65% or low- approximately 30% carbohydrate intake) regimen designed to manipulate muscle glycogen concentrations. Movement and technical parameters of performance and selected physiological responses were measured. Pre-game muscle glycogen concentrations following the high carbohydrate diet (mean +/- SD) (395.6 +/- 78.3 mmol x kg(-1) dw) were significantly higher than following the low carbohydrate diet (287.1 +/- 85.4 mmol x kg(-1) dw). The results of the movement analysis showed that the players performed significantly more (approximately 33%) high intensity exercise in the game played following the high carbohydrate diet. No significant differences were found, between the two dietary conditions, in any of the measured technical variables. Plasma FFA and glycerol concentrations in the game played following the low carbohydrate diet were significantly higher after 45 min (905 +/- 103 and 293 +/- 23 micromol x l(-1)) and post exercise (1388 +/- 122 and 366 +/- 36 micromol x l(-1)) compared to the game played following the high carbohydrate diet (532 +/- 137 and 202 +/- 55 micromol x l(-1) and 888 +/- 192 and 266 +/- 27 micromol x l(-1), respectively). Post-exercise blood glucose levels were significantly lower in the game played following the low carbohydrate diet (5.8 +/- 0.3 vs 7.2 +/- 0.3 mmol x l(-1)). No significant differences were found in the mean blood lactate values (3.5 +/- 0.6 and 3.9 +/- 0.5 mmol x l(-1)) or mean heart rates (162 vs. 163.5 beats x min(-1)) between the high and low carbohydrate conditions, respectively. The main finding from this study was that the carbohydrate content of the diet influenced the amount of high intensity exercise performed during a small-sided football game. This suggests that to optimise performances, in not only football but possibly also other multiple sprint sports of similar duration, a high carbohydrate diet should be administered in preparation for intense training and competition.